HUBUNGAN ANTARA PERSEPSI SISWA TERKAIT GURU MATA PELAJARAN TIK DALAM MENGAJAR DAN SUMBER BELAJAR TERHADAP HASIL BELAJAR TIK - I Nyoman Sumadiyasa; I Gede Mahendra Darmawiguna; Dessy Seri Wahyuni (Universitas Pendidikan Ganesha, 2014)
Tthis study aimed to (1) know the correlation between students’ perception to the teacher who teached TIK toward the result in learning TIK at the eighth and ninth grade students in SMP Negeri 3 Penebel; (2) know the correlation between the source of learning toward the result in learning TIK at eighth and ninth grade in SMP Negeri 3 Penebel; (3) know the correlation among students’ perception and the source of learning toward the result of students in learning TIK at eighth and ninth grade in SMP Negeri 3 Penebel. Ex post Facto was the method which used in this study because there was no special treatment or manipulation used toward the variable. The study only covered the data which were had by the respondents. This study was conducted at eighth and ninth grade in SMP Negeri 3 Penebel in the second semester at the academic year 2013/2014. The total sampel of this study is 176 students. The result of the study showed that the students’ perception toward the teacher who teached TIK determined the result of students in learning TIK at eighth and ninth grade in SMP Negeri 3 Penebel. The result of the anlysis showed (1) There was no significant correlation between students’ perception toward the teaher in teaching TIK to the result of students in learning TIK; (2) there was no significant correlation between students’ source of learning toward the result of students’ learning; and (3) There was no a significant correlation among students’ perception to the teacher who teached TIK and students’ source in learning TIK toward the result in learning TIK.